A Molluscicidal Triterpenoid Saponin from the Fruits of Napoleonaea P. Beauv (Lecythidaceae) - Chukwunonye M Ojinnaka; Dorothy C Okpala (Journal of Applied Sciences and Environmental Management)
Click on the link to view the abstract.